Al-Isytiqāq dalam Linguistik Arab Perspektif Ibnu Jinni - Mahdiyyah, Syahda A'immatul; Pribadi, Mohammad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research aims to discuss more deeply one of the thoughts or ideas of one of the linguistic figures, namely Ibn Jinni, about Isytiqāq or derivation, which then the discussion was also discussed by modern linguists. This research is included in the type of qualitative research based on literature studies or library research. Researchers collect data from data sources in the form of books or Ibn Jinni’s books and supported by related journals. Data is collected by reading and recording techniques, namely reading some existing references and then recording the form of Isytiqāq in the book al-Khaṣāiṣ by Ibn Jinni. After the data is collected, the data is analyzed with content analysis techniques and presented using systematic language. As for Isytiqāq according to Ibn Jinni, there are two types of Isytiqāq, namely Isytiqāq, namely al-Isytiqāq as-Aṣgar or now commonly known as Isytiqāq Am or Isytiqāq Tahshrifiyyah and al-Isytiqāq al-Akbar or now generally known as qalb.